2017
DOI: 10.3315/jdcr.2017.1241
|View full text |Cite
|
Sign up to set email alerts
|

"Clown nose" as first manifestation of squamous cell carcinoma of the lung

Abstract: Background: Skin metastases occur in 0.7% to 9% of all patients with cancer and are usually considered a late event in the evolution of most visceral carcinomas. The development of a nodular metastatic lesion on the nasal tip is known as clown nose sign. Main observation:We report a 64-year-old man that developed a nodular lesion on his nasal tip as first manifestation of squamous lung carcinoma. Conclusion:The biopsy of the cutaneous metastasis may be helpful to histopathologically confirm the suspected prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
2
Order By: Relevance
“…In addition to lung cancer, it has also been reported in hepatocellular carcinoma, esophageal cancer, seminoma, chordoma, leukemia, breast cancer, and cervical cancer. 12 , 13 The mechanism of development of lung cancer metastases to the nasal skin is not fully understood. It is suggested that lung cancer cells can be transported through the pulmonary vessels and the lymphatic system to distant locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to lung cancer, it has also been reported in hepatocellular carcinoma, esophageal cancer, seminoma, chordoma, leukemia, breast cancer, and cervical cancer. 12 , 13 The mechanism of development of lung cancer metastases to the nasal skin is not fully understood. It is suggested that lung cancer cells can be transported through the pulmonary vessels and the lymphatic system to distant locations.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous metastasis on the nasal tip is known as “clown nose”. 12 , 13 It is important to distinguish suspected lesions from common non-melanoma skin cancers and less frequent tumors such as amelanotic melanoma, primary cutaneous lymphomas, and inflammatory lesions. 1 We report two patients with a tumor on the nose, which proved to be the first sign of the metastatic lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Squamous cell carcinoma (SCC) is much less common to involve the nose, although possible, and among them, most neoplasms are keratinizing squamous cell carcinomas that usually originate from the sinonasal tract [ 15 ]. There has also been a report of lung cancer metastasizing to the nose with “clown nose” as the presenting symptom [ 16 ]. However, three sets of biopsies were done in this patient which ruled out any of these malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Las metástasis cutáneas son diseminaciones de células malignas en la piel procedentes de tumores a distancia 6 . Se consideran manifestaciones infrecuentes de neoplasias porque se presentan en el 0.7% a 9% de todos los pacientes con cáncer y deben sospecharse en pacientes con lesiones de rápido crecimiento sin respuesta al tratamiento médico 7 . Se calcula que aparecen uno a tres años después del diagnóstico del tumor primario 8 .…”
Section: Comentariounclassified